2014
DOI: 10.1016/j.biomaterials.2013.12.039
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mesenchymal stem cell sheets on structural allograft healing of critical sized femoral defects in mice

Abstract: Structural bone allografts are widely used in the clinic to treat critical sized bone defects, despite lacking the osteoinductive characteristics of live autografts. To address this, we generated revitalized structural allografts wrapped with mesenchymal stem/progenitor cell (MSC) sheets, which were produced by expanding primary syngenic bone marrow derived cells on temperature-responsive plates, as a tissue engineered periosteum. In vitro assays demonstrated maintenance of the MSC phenotype in the sheets, sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 48 publications
2
90
0
2
Order By: Relevance
“…However, this did not completely mimic an autograft as slower resorption of the graft was observed [103]. More recently it has been reported that BM-MSC cell sheets can act as an engineered periosteum and promote bone callus formation during allograft healing [104], while PDC cell sheets may have applications in tendon-bone healing [105]. Evidently, the investigation of periosteum mimetics for skeletal regeneration and repair is gathering pace and further investigation is eagerly anticipated.…”
Section: Tissue Engineering Strategies Mimicking the Periosteum In Itmentioning
confidence: 96%
“…However, this did not completely mimic an autograft as slower resorption of the graft was observed [103]. More recently it has been reported that BM-MSC cell sheets can act as an engineered periosteum and promote bone callus formation during allograft healing [104], while PDC cell sheets may have applications in tendon-bone healing [105]. Evidently, the investigation of periosteum mimetics for skeletal regeneration and repair is gathering pace and further investigation is eagerly anticipated.…”
Section: Tissue Engineering Strategies Mimicking the Periosteum In Itmentioning
confidence: 96%
“…24 One study (3%) used a mouse model and investigated the femur. 48 One (3%) study used both rabbit and mice models in their study and investigated the radius. 22 …”
Section: Evaluation Of Animal Modelmentioning
confidence: 99%
“…Considering the wide diversity of conducted research, investigators should be extremely cautious to translate conclusion in-between models and species and pay special attention in designing the animal studies to draw valuable and reproducible results. Mouse: [185], [186] Rat: [187] (DM), [188] Rabbit: [189], [190], [191], [192] Dog: [193], [194] Sheep/Goat: [167], [170], [176], [195], [196], [197] human BM-derived MPCs…”
Section: Animal Models In Cell-based Therapiesmentioning
confidence: 99%